TINJAUAN KRIMINOLOGI TERHADAP ANAK SEBAGAI PELAKU BEGAL SEPEDA MOTOR YANG MENGGUNAKAN SENJATA TAJAM (Studi Kasus Di Wilayah Hukum Kepolisian Resort Palu) - Moh Ihsan; Muliadi Muliadi (Maleo Law Journal, 2020)
One form of crime that often happens in every region and that is often discussed is begal by using a motorized vehicle. This crime is identified with various cases of violence on the streets, but in the Big Indonesian Dictionary, the word "begal" is interpreted as deprivation on the road, meaning that this crime is equated with cases of theft with violence because the act was preceded, accompanied or followed by violence or threats of violence. . The purpose of this study was to examine what factors led to the emergence of motorcycle boots using sharp weapons in the Palu District Police jurisdiction, what efforts were made by the Palu Police Officers in tackling motorcycle boots using sharp weapons in the city of hammer. The research method uses the type of normative-empirical research or also called sociological (non-doctrinal) legal research. In addition to the type of research, it is also necessary to determine the nature of the research to be applied to the focus of the object of research. The nature of the study is the characteristics of research that describes the division of objectives or classification of research objects that will be used by researchers to carry out research. The analysis technique used in this study is qualitative analysis which is an analytical technique that uses deductive-inductive techniques through reasoning and legal argumentation for all research data.Keywords: Criminology. Son Robber